NEED FOR INTEGRATING PRE-SCHOOL TO ELEMENTARY EDUCATION - Singh, Ram Pal (THE PRIMARY TEACHER, 2011)
Learning starts from birth. Children learn through interactions with social, physical and cultural environment provided to them. Early childhood experiences are, therefore, important from the point of view of helping them to learn better during primary stage and beyond. The present article highlights the need for good quality pre-school education for all children and integrating it with elementary education in order to improve the quality of education